RARE-08. Profiling of recurrent adamantinomatous cranionpharyngioma confirms the activation of the MAPK pathway and identifies copy number aberrations in relapsed tumours. (3rd June 2022) - Apps, John; Pickles, Jessica; Stone, Thomas; Chalker, Jane; Ogunbiyi, Olumide; Schwalbe, Edward; Brandner, Sebastian; Otto, Georg; Castellano, Sergi; Jacques, Thomas; Deutschbein, Timo; Martinez-Barbera, Juan Pedro
Abstract: Craniopharyngiomas are rare challenging tumours, with around 25% of cases recurring despite surgery and/or radiotherapy. Whilst transcriptomic and proteomic profiling of adamantinomatous craniopharyngioma (ACP) have revealed activation of the MAPK pathway and IL-6 mediated inflammation, relatively little is known about the biological processes involved in tumour recurrence. To address this, we have analysed a cohort of primary and relapsed ACP tumour accessed from tissue banks, local pathology departments and international collaborators. Serial samples of recurrent ACP (n=11), recurrent papillary craniopharyngioma (PCP) (n=4) and 3 non-recurrent ACP were analysed using β-catenin, pERK1/2 immunostaining, DNA methylation array and RNA sequencing. Differential expression and methylation analyses confirmed differences between ACP and PCP, with over representation of WNT pathway genes in ACP and the MAPK pathway genes in PCP. All of the primary and all except for one of the relapsed ACP tumours showed a pERK1/2 expression. Differences in the immune environment were also identified between ACP and PCP, with higher levels of some inflammatory mediators and CD14+ cell signatures in PCP compared with ACP. Whilst differential methylation and expression analysis revealed relatively stable methylomes and transcriptomes between serial samples of cases, segmental chromosomal alterations were identified in recurrence samples from five ACP cases (5/11, 45%). One relapsed case showed histological and molecular signs of malignant transformation, including high ki67 and deletion of TP53 . Surprisingly, this malignant tumour showed nuclear beta-catenin in all neoplastic epithelial cells and absence of pERK1/2 staining, despite the primary tumour showing the typical beta-catenin and pERK1/2 expression patterns. These results suggest that the molecular landscape of craniopharyngioma remains stable between recurrences in most cases, but, there is evidence of molecular evolution in a subset of cases. Activation of the MAPK pathway in the vast majority of ACP tumours supports the clinical evaluation of MAPK pathway inhibitors in ACP patients.